Spectral domain optical coherence tomography with extended depth-of-focus by aperture synthesis - Bo, En (2018)
We developed a spectral domain optical coherence tomography (SD-OCT) with an extended depth-of-focus (DOF) by synthetizing aperture. For a designated Gaussian-shape light source, the lateral resolution was determined by the numerical aperture (NA) of the objective lens and can be approximately maintained over the confocal parameter, which was defined as twice the Rayleigh range. However, the DOF was proportional to the square of the lateral resolution. Consequently, a trade-off existed between the DOF and lateral resolution, and researchers had to weigh and judge which was more important for their research reasonably. In this study, three distinct optical apertures were obtained by imbedding a circular phase spacer in the sample arm. Due to the optical path difference between three distinct apertures caused by the phase spacer, three images were aligned with equal spacing along z-axis vertically. By correcting the optical path difference (OPD) and defocus-induced wavefront curvature, three images with distinct depths were coherently summed together. This system digitally refocused the sample tissue and obtained a brand new image with higher lateral resolution over the confocal parameter when imaging the polystyrene calibration beads.